Analysis of temporal and spatial changes and influencing factors of sewage treatment rates of small towns in Chongqing - Zhou, Chao; Yu, Zhihan; Wang, Qin (Frontiers in Environmental Science, 2023)
Small towns are the bridge between urban and rural areas, and their sewage treatment is the focus and problem of the urban construction. With Chongqing as the research object, this paper explores the influencing factors and the characteristics of temporal and spatial changes of sewage treatment rates of 756 small towns in Chongqing from 2014 to 2020 from four aspects: the overall situation, space, population and industry. The results show that 1) the sewage treatment rates of small towns showed a certain trend of improvement since 2014, and the polarization between small towns continued to decrease. 2) The sewage treatment rates of small towns presented a significant spatial correlation in the entirety, but the correlation weakened year by year. In 2014, the sewage treatment rates of small towns were mainly high-high cluster, while those in 2017 were mainly low-low cluster and in 2020, low-low cluster in a scattered manner. 3) The sewage treatment rates of small towns with a population of 40,000 to 60,000 and over 60,000 in 2014 were relatively high, but the gap narrowed year by year. Small towns with more than 60,000 people had the highest sewage treatment rate in 2020, but the gap between the lowest values reduced to 11.94%. 4) In 2014, small towns with tourism as the leading industry had a significant advantage, but three types of small towns including industrial and mining ones, were improving fast. 5) Land urbanization, radiation effect of county towns, investment in the urban construction, population size and leading industry all had obvious driving effects on the increase of sewage treatment rates of small towns, but the impact of urban construction investment was relatively weak because it contained a large scale of real estate investment.